Psychoinformatics: a theoretical approach on information science and psychology - Pandey, Deepti (Journal of Management and Science, 2020)
This article provides insight into an emerging research discipline called Psychoinformatics.In the context of Psychoinformatics, we emphasize the co-operation between the disciplines of Psychology and Information Science which handles large data sets is derivative from severely used devices like smartphones or any online social networking in order to highlight sychological qualities including both personality and mood. New challenges await psychologists considering the result “Big Data” sets because classic psychological methods will only in part be able to analyze this data derived from ubiquitous mobile devices as well as other everyday technologies. Consequently, psychologist must enrich their scientific methods through the inclusion of methods from informatics. Furthermore, we also emphasize on data which is derived from Psychoinformatics to combine in a such a way to give meaningful way with data from human neuroscience. We close the article with some observations of areas for future research and problems that require consideration within this new discipline.